Fasilitas Olahraga Indoor Di Kota Merauke (Pendekatan Arsitektur Neo Vernacular) - Syafrin Yusuf; Biatma Syanjayanta; Dina Pasalolo (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2020)
sports that facilitate a variety of indoor sports in the city of Merauke are inadequate. Neo Verracular is an architectural design concept that mixes modern aspects and traditions, so an indoor sports facility design in Merauke City is needed with the Neo Vernacular Architecture Approach. Using the Descriptive Method to determine the elements, traits, traits or phenomena. This method starts by collecting data and analyzing data that is carried out through survey techniques, case studies, comparative studies, studies of time and motion, behavior analysis and documentary analysis. The data obtained will be used as a reference in the Design of Indoor Sports Facilities in the City of Merauke with the Neo Vernacular Architecture Approach.